Estudo Fitoquímico de Abarema cochliacarpos (Gomes) Barneby & J. W. Grimes e Calliandra depauperata Benth - Pires, Andreza Maria Lima (2011)
This work describes the chemical investigation of plants from the genera Abarema and Calliandra both belonging to Leguminosae family. The chemical prospection of Abarema cochliacarpos resulted in the isolation of 11 substances while from Calliandra depauperata was isolated 10 compounds. From EtOH extracts of different parts of A. cochliacarpos (wood, wood bark and leaves) were isolated and characterizated of steroids: spinasterol, 3-O-β-D-glucopiranosyl-spinasterol and 3-O-β-D-(6’-O-dodecanoil)-glucopiranosyl-spinasterol), the mixture triterpenes oleanolic and ursolic acids; the flavonoids catechin, taxifolin, miricetrin and 3’,4’,7,8-tetrahydroxyflavonol, besides of galic acid and ethyl galate. Compound 3-O-β-D-(6’-O-dodecanoil)-glucopiranosyl-spinasterol) was isolated for the firs time. From roots EtOH extract of C. depauperata were isolated the flavonoids 5-methoxy-3’,4’,7-trihydroxyflavone; 3’,4’,7-trihydroxyflavone and 4’,6’,7-trimethoxy-3’-hydroxyflavone; the cassane diterpenes: 7β,17-dihydroxy-12-oxo-cassan-13,15-diene, 15,16-bisnor-7β,17-dihydroxy-12-oxo-cassan-13-ene and depauperatin, besides the fatty esters bis-(2,3-dihydroxypropil) tetracosanodioate, bis-(2,3-dihydroxypropil) docosanodioate, 24-hydroxy-tetracosanoate-2,3-dihydroxypropil and 26-hydroxy-hexacosanoate-2,3-dihydroxypropil. Compounds 4’,6’,7-trimethoxy-3’-hydroxyflavone; 15,16-bisnor-7β,17-dihydroxy-12-oxo-cassan-13-ene and depauperatin, and all fatty esters are being reported for the first time. The structural determination of all secondary metabolites isolated in this work involved spectrometric techniques such as: IR, MS and NMR including 2D (COSY, HMQC, HMBC e NOESY) experiments, as well as, comparison with published data